(untitled) (Ameghiniana, 2013)
In this paper the author develops a systematic study of the Coniferopsida found in the paleophytological gondwanic association of Monte Mor, Sáo Paulo State, Brazil, which were described in the D. Sc, thesis, University of Sáo Paulo. The fossil plants, preserved like impressions, are represented by the following species: Noeggerathiopsis hislopii, Paranocladus? fallax and Buriadia heterophylla, mentioned for first time in Itu Formation (Upper Carboniferous), Tubaráo Group of Sáo Paulo State.